Deploying a GIS for Enhancing Clinic Accessibility in Indonesia: An Agile QGIS Approach - Prananingrum, Lely; Sari, Ilmiyati; Harahap, Robby Kurniawan (Journal of Information Systems and Informatics, 2025)
Health is a fundamental necessity for all living beings, and clinics represent one of the most accessible healthcare facilities for communities. The spatial distribution of clinics can be effectively analysed and visualized through a Geographic Information System (GIS). This study proposes the development of a web-based clinic GIS for Indonesia using Quantum GIS (QGIS) software, implemented through the Agile methodology. The integration of Agile practices ensures that the system is accurate, adaptable, and responsive to evolving user needs. The resulting GIS website was successfully developed and tested, achieving a usability score of 88.76%, with effectiveness, efficiency, and satisfaction ratings of 91%, 90%, and 85%, respectively. The platform aims to support policymakers and healthcare providers in gaining a deeper understanding of health service distribution, ultimately promoting more equitable, data-driven decision-making in healthcare planning and resource allocation.
Keywords: Clinic, QGIS, Geographic Information System, Website, Agile